Effects of Structure Parameters of Gravity-Type Heat Pipe on Heat Transfer Characteristics for Waste Heat Recovery from Mine Return Air - Yu Zhai; Zhikun Ling; Xu Zhao; Zhifeng Dong (Energies)
In the condition of waste heat recovery from mine return air with a temperature of 20~30 °C and velocity about 4 to 8 m/s, the structure of gravity-type heat pipe with fin increases the heat exchange areas and meanwhile increases the resistance of air flow, which consumes a large amount of main fan power driven by a motor. Furthermore, the resistance of air flow increases greatly with the velocity of the air flow. In this paper, the gravity-type heat pipe with elliptical smooth surface is studied to decrease the resistance and loss of energy of the air flow. In order to obtain the influence of ellipticity on heat transfer efficiency and energy loss under the condition of a certain heat transfer area of the heat pipe, the heat transfer efficiency of a single pipe and a pipe bundle with different ellipticities is studied by using numerical simulation based on the equal section perimeter. The results show that the reasonable change of ellipticity can increase specific enthalpy and decrease entropy production. When the pipe is single, the ellipticity is 0.56 and the specific enthalpy is the largest, increasing by 12.08%. The ellipticity of the pipe bundle is 0.61, and the specific enthalpy is the largest, increasing by 19.28%. The entropy production slightly increased by 10.4%. Moreover, the empirical formula of single pipe heat transfer with an error less than 5% and the empirical formula of pipe bundle heat transfer with an error less than 2.2% are obtained. The empirical formula of pipe bundle heat transfer at different temperatures is modified, and the error is less than 5%, which provides the fundamental data for deep research, development, and engineering design of gravity-type heat pipe heat energy exchange system of underground return airflow in coal mines.